ARCHIGESH 2023 - Evseeva, Elena; Tsoy, Valery (project baikal, 2023)
The article provides an overview of ARCHIGESH 2023, a festival of the ski club of architects. The festival’s areas of focus, its main events and its participants are presented. The ARCH-CONCEPT educational programme, as well as entertainment and sports programmes are described.
Keywords: ARCHIGESH 2023; ski club of architects; business, sports, entertainment blocks; winners; contests